2bRAD-M reveals differences in microbial communities between Modic changes and disc herniation - Yang, Fang; Zhang, Jingtao; Zha, Junpu; Zhang, Guolei; Li, Jia; Du, Wei; Liu, Lin; Di, Jun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundModic changes are caused by various factors, such as degenerative processes, inflammation, biomechanical, genetic, and metabolic factors, infection, and smoking. Bacteria have been identified in human intervertebral discs by 16S rRNA sequencing; however, the low microbial biomass in intervertebral disc tissue limits species-level analyses using this approach. In this study, we employed 2bRAD-M (2b Restriction Site Associated DNA sequencing for Microbiome), a new sequencing technology capable of accurately characterizing bacteria, fungi, and archaea in samples with low microbial biomass at species-level resolution.MethodsWe surveyed 20 intervertebral disc (IVD) samples, including 10 IVD samples with Modic changes and 10 herniated disc samples. 2bRAD-M was performed to explore whether microbial differences existed between Modic change and herniated disc samples.ResultsIn total, 332 microbial species were identified, including 75 species shared between the two groups. Enrichment for Escherichia_coli, Cupriavidus_pauculus, and Bradyrhizobium_denitrificans was observed in the Modic change group, while Afipia_broomeae, Phyllobacterium_calauticae, Tardiphaga_sp002256345, Mesorhizobium_sp004136315, Afipia_sp000497575, Burkholderia_contaminans, and Afipia_sp017474385 were more abundant in the herniated disc group. Additionally, 19 discriminatory taxa were determined by linear discriminant analysis effect size (LEfSe). In a random forest model for partitioning the two groups, the species with the highest variable importance were Afipia_broomeae, Phyllobacterium_calauticae, and Escherichia_coli. Moreover, a newly constructed random forest model based on an optimal marker set consisting of eight highly abundant species successfully distinguished between the Modic change and herniated disc groups, with an accuracy of 81.0%. A functional annotation analysis showed that differentially abundant taxa between the Modic change and herniated disc groups could be assigned to 4093 COGs (Clusters of Orthologous Groups) and 342 related signaling pathways.ConclusionThis study represents the first application of 2bRAD-M to Modic changes and disc herniation, revealing significant differences in microbial taxa between the two groups. These results suggest that microbial dysbiosis in the intervertebral disc is associated with Modic changes and provide candidate targets for further studies of the mechanisms underlying the development and progression of Modic changes.